2007
DOI: 10.1016/j.ajog.2007.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia regulates the expression of fatty acid–binding proteins in primary term human trophoblasts

Abstract: Objective-Fatty acids (FA) are essential for fetal development. Cellular FA uptake is modulated by fatty acid binding proteins (FABPs). We hypothesized that hypoxia regulates the expression of FABPs in human trophoblasts.Study design-Primary term human trophoblasts were cultured for 72 h in either standard (O 2 = 20%) or hypoxic (O 2 < 1%) conditions. FABP expression was interrogated using PCR and western immunoblotting. Trophoblast lipid droplets were examined using BODIPY 493/503 staining.Results-We detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 27 publications
7
71
0
Order By: Relevance
“…Our findings are in keeping with those of Biron-Shental et al [7] who described an increase in FABP1, FABP3 and FABP4 protein expressions in primary cultured trophoblast cells in response to 48 h of exposure to gaseous hypoxia (O 2 o 1%). Mishima et al [8] showed that FATP2 mRNA levels were increased in primary cultured trophoblasts cultured for 48 h in gaseous hypoxia (O 2 o 1%).…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Our findings are in keeping with those of Biron-Shental et al [7] who described an increase in FABP1, FABP3 and FABP4 protein expressions in primary cultured trophoblast cells in response to 48 h of exposure to gaseous hypoxia (O 2 o 1%). Mishima et al [8] showed that FATP2 mRNA levels were increased in primary cultured trophoblasts cultured for 48 h in gaseous hypoxia (O 2 o 1%).…”
Section: Discussionsupporting
confidence: 95%
“…2A). CoCl 2 is a well-described hypoxiamimetic agent [7,12,14] but also activates the nuclear transcription factor NF-κB [15]. There are two putative κB elements within the FABP3 gene at À 834 and À 825 bp that are presumably responsible for this increase in luciferase activity (data not shown).…”
Section: Hypoxia Induces Fabp3 Expressionmentioning
confidence: 86%
See 1 more Smart Citation
“…This may be explained by the fact that improved oxygenation is a protective factor and decreases A-FABP expression. Similar findings were noted in in vitro studies 20 . This also confirms the conclusion by Lam et al 15 that different intensity of intermittent hypoxia in OSA subjects results in different degrees of heightened expression of A-FABP.…”
Section: Discussionsupporting
confidence: 77%
“…These findings suggests that there may be a threshold effect of OSA on FABP levels and that FABP levels may be upregulated mainly in those subjects with high AHI and a more severe degree of hypoxaemia. There is scanty information regarding the regulation of FABP, although there has been previous evidence of FABP expression being regulated by hypoxia in human trophoblasts in vitro [28]. It is possible that the different intensity of intermittent hypoxia in OSA subjects results in different degrees of heightened expression of A-FABP, which then assumes a mediating role between OSA and metabolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%